Exogenous gene integration mediated by genome editing technologies in zebrafish. Issue 3 (4th May 2017) - Morita, Hitoshi; Taimatsu, Kiyohito; Yanagi, Kanoko; Kawahara, Atsuo
ABSTRACT: Genome editing technologies, such as transcription activator-like effector nuclease (TALEN) and the clustered regularly interspaced short palindromic repeat (CRISPR)/CRISPR-associated protein (Cas) systems, can induce DNA double-strand breaks (DSBs) at the targeted genomic locus, leading to frameshift-mediated gene disruption in the process of DSB repair. Recently, the technology-induced DSBs followed by DSB repairs are applied to integrate exogenous genes into the targeted genomic locus in various model organisms. In addition to a conventional knock-in technology mediated by homology-directed repair (HDR), novel knock-in technologies using refined donor vectors have also been developed with the genome editing technologies based on other DSB repair mechanisms, including non-homologous end joining (NHEJ) and microhomology-mediated end joining (MMEJ). Therefore, the improved knock-in technologies would contribute to freely modify the genome of model organisms.